1999
DOI: 10.1128/mmbr.63.4.968-989.1999
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium -Legume Symbiosis and Nitrogen Fixation under Severe Conditions and in an Arid Climate

Abstract: SUMMARY Biological N2 fixation represents the major source of N input in agricultural soils including those in arid regions. The major N2-fixing systems are the symbiotic systems, which can play a significant role in improving the fertility and productivity of low-N soils. The Rhizobium-legume symbioses have received most attention and have been examined extensively. The behavior of some N2-fixing systems under severe environmental conditions such as salt stress, drought stress, acidity, alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
684
3
40

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,348 publications
(752 citation statements)
references
References 333 publications
25
684
3
40
Order By: Relevance
“…Overall, the in vitro tolerance of strains to salinity was quite high because about 20% of them grew at the maximum level tested of 1034 mM NaCl (corresponding to 6% NaCl w/v). Our findings are in agreement with previous studies reporting that rhizobia isolated from woody legumes in general and from dry-zone Acacia species in particular tolerated such high salinity levels (Zahran, 1999;Mohamed et al, 2000;Diouf et al, 2007;Essendoubi et al, 2007). In accordance with previous reports (Zahran, 1999), we found Bradyrhizobium strains less tolerant, although originating from saline ecosystems in our study (coastal dunes), than fast-growing Rhizobium, Ensifer, and Ochrobactrum strains that tolerated up to 1034 mM NaCl.…”
Section: Discussionsupporting
confidence: 94%
“…Overall, the in vitro tolerance of strains to salinity was quite high because about 20% of them grew at the maximum level tested of 1034 mM NaCl (corresponding to 6% NaCl w/v). Our findings are in agreement with previous studies reporting that rhizobia isolated from woody legumes in general and from dry-zone Acacia species in particular tolerated such high salinity levels (Zahran, 1999;Mohamed et al, 2000;Diouf et al, 2007;Essendoubi et al, 2007). In accordance with previous reports (Zahran, 1999), we found Bradyrhizobium strains less tolerant, although originating from saline ecosystems in our study (coastal dunes), than fast-growing Rhizobium, Ensifer, and Ochrobactrum strains that tolerated up to 1034 mM NaCl.…”
Section: Discussionsupporting
confidence: 94%
“…2013), and comparable contributions of newly fixed N to P. pallida foliar N at the two sites would result in far greater contributions of newly fixed N to lowland soils where productivity and litterfall are higher. While our estimates of the proportion of foliar N derived from fixation at upland and lowland sites overlapped during the period the reference plant was present, the rates of both fixation and nutrient uptake from soils tend to be reduced in legumes experiencing water stress (DeVries et al 1989, Serraj et al 1999, Zahran 1999, Abdelhamid et al 2011). Reduced fixation rates can be due to reductions in the availability of photosynthetic products that follow drought (Kuo andBoersma 1971, Nambiar et al 1983), reductions in O 2 availability for nodule respiration (Denison 1998), and feedback regulation by N compounds (Parsons et al 1993); all three of these processes are likely to be exacerbated by reductions in leaf water potential, such as those seen at upland plots, and hence phloem flow rates (Serraj et al 1999).…”
Section: Coupling Of Hydrological C and Nutrient Cyclesmentioning
confidence: 70%
“…For example, the distribution of Acacia species across saline and alkaline environments is strongly influenced by evolutionary history (Bui et al 2014). Likewise, rhizobial abundance and diversity can be strongly influenced by edaphic conditions [e.g., soil pH and fertility, salinity, temperature, and rainfall (Alexander et al 1996;Zahran 1999;Thrall et al 2009)]. Some studies have further suggested that the relative dominance of different rhizobial genera may shift in relation to environmental stress (Barnet and Catt 1991;Jenkins 2003).…”
Section: Discussionmentioning
confidence: 99%